2017
DOI: 10.1111/1751-7915.12771
|View full text |Cite
|
Sign up to set email alerts
|

The parasporal crystals of Bacillus pumilus strain 15.1: a potential virulence factor?

Abstract: Summary Bacillus pumilus strain 15.1 was previously found to cause larval mortality in the Med‐fly Ceratitis capitata and was shown to produce crystals in association with the spore. As parasporal crystals are well‐known as invertebrate‐active toxins in entomopathogenic bacteria such as Bacillus thuringiensis (Cry and Cyt toxins) and Lysinibacillus sphaericus (Bin and Cry toxins), the B. pumilus crystals were characterized. The crystals were composed of a 45 kDa protein that was identified as an oxalate decarb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Several strains were susceptible to Bp15.1PLP particles ( Table 7 ), showing a clear halo when a drop of a suspension of Bp15.1PLP (and Bp15.1Hope) was placed over the strain in a spot test. All of the susceptible strains were B. pumilus strains, including B. pumilus 15.1C, an extra-chromosomal DNA cured strain obtained from B. pumilus 15.1 and previously described by our group [ 5 ]. Bp15.1Hope was not able to form plaques in any of the strains tested in lawn assays (data not shown), so the halos observed seem to indicate that Bp15.1PLP has a strong bacteriocin-like activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several strains were susceptible to Bp15.1PLP particles ( Table 7 ), showing a clear halo when a drop of a suspension of Bp15.1PLP (and Bp15.1Hope) was placed over the strain in a spot test. All of the susceptible strains were B. pumilus strains, including B. pumilus 15.1C, an extra-chromosomal DNA cured strain obtained from B. pumilus 15.1 and previously described by our group [ 5 ]. Bp15.1Hope was not able to form plaques in any of the strains tested in lawn assays (data not shown), so the halos observed seem to indicate that Bp15.1PLP has a strong bacteriocin-like activity.…”
Section: Resultsmentioning
confidence: 99%
“…The enzyme can catalyse the transformation of oxalate to formate, a previously recognised neurotoxic compound. It has been proposed that oxalate decarboxylase could be a potential virulence factor [ 5 ], although the mechanism of toxicity is still under study.…”
Section: Introductionmentioning
confidence: 99%
“…Sixteen papers were analysed in depth. Eleven had methodological problems with regard to the identification procedures (Danilova et al., ; Garcia‐Ramon et al., ; Osman et al., ; Joshi et al., ; Shah et al., ,b; Li et al., ; Tsonis et al., ), source attribution (Allam et al., ; Joshi et al., , Shah et al., ,b) or were not food related (Aydin et al., ).…”
Section: Assessmentmentioning
confidence: 99%
“…The gene belongs to the phage 6 region and has been recruited by the sporulation process with its expression dependent on sigma(K). OxD is a spore coat inner layers constituent (Costa et al, 2004 ), identified in crystalline form in B. pumilus (Garcia‐Ramon et al, 2018 ).…”
Section: The Crucial Role Of Metalsmentioning
confidence: 99%